Isolation and Analysis of Hematopoietic Stem Cells from the Placenta - Gekas, Christos (MyJove Corporation, 2008)
Hematopoietic stem cells (HSCs) have the ability to self-renew and generate all cell types of the blood lineages throughout the lifetime of an individual. All HSCs emerge during embryonic development, after which their pool size is maintained by self-renewing cell divisions. Identifying the anatomical origin of HSCs and the critical developmental events regulating the process of HSC development has been complicated as many anatomical sites participate during fetal hematopoiesis. Recently, we identified the placenta as a major hematopoietic organ where HSCs are generated and expanded in unique microenvironmental niches (Gekas, et al 2005, Rhodes, et al 2008). Consequently, the placenta is an important source of HSCs during their emergence and initial expansion. In this article, we show dissection techniques for the isolation of murine placenta from E10.5 and E12.5 embryos, corresponding to the developmental stages of initiation of HSCs and the peak in the size of the HSC pool in the placenta, respectively. In addition, we present an optimized protocol for enzymatic and mechanical dissociation of placental tissue into single-cell suspension for use in flow cytometry or functional assays. We have found that use of collagenase for single-cell suspension of placenta gives sufficient yields of HSCs. An important factor affecting HSC yield from the placenta is the degree of mechanical dissociation prior to, and duration of, enzymatic treatment. We also provide a protocol for the preparation of fixed-frozen placental tissue sections for the visualization of developing HSCs by immunohistochemistry in their precise cellular niches. As hematopoietic specific antigens are not preserved during preparation of paraffin embedded sections, we routinely use fixed frozen sections for localizing placental HSCs and progenitors.